DICTIONARY OF FEMINITIVES AS ATTEMPT OF FORMING THE LANGUAGE OF LES MARTOVICH - Brus M. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article shows an attempt to lexicographically organize and systematize feminitives on the basis of artistic creativity of Les Martovich, which may serve as a source for the formation of the "Dictionary of the Language of Les Martovich", as well as for the full "Dictionary of feminitives of the Ukrainian language". On the basis of the "Feminitive Dictionary", the names of women of Ukrainian and foreign origin were analyzed, commonly used words, regionalisms and dialecticisms were noted, their relevance in expressing the realities of modern women’s life was pointed out.